The effects of health promotion on girls' and young women's health behaviours - Mitchell, Helen; Shoebridge, Andrea; Howat, Peter; Cross, Donna; O'Farrell, I. (WA Centre for Health Promotion Research, 2007)
This formative research examines the effects of health promotion on girls' and young women's health behaviours. Health promotion campaigns targeting women have previously had variable success. Some have been criticised for containing unhelpful values and messages, for example, those that were seen to cause harm to women outside the target population or use of stereotypical symbolism to support the message. Within this study these are called 'unintended consequences'. The Young Women and Health Promotion (YW&HP) study examines the potential for unintended consequences (both negative and positive) of health promotion in general. The focus is then narrowed to examine in more detail whether the use of specific methodologies (such as social marketing), contribute to unintended consequences when promoting physical activity, nutrition and non- smoking messages to girls' and young women. These health behaviours were specifically targeted as they are known to be the major modifiable risk factors for women in the prevention of many chronic illnesses.This formative research involved the collection and analysis of qualitative and quantitative data from 132 girls and young women across three age categories. These were Year 7 girls (Children - 11-12 years), Year 10 girls (Adolescents - 14-15 years) and young adults (18-25 years). Eighteen focus groups and 15 in-depth interviews were conducted to elicit responses to examine the effects of health promotion on girls' and young women's health behaviours, with particular focus on unintended effects. Current and past health promotion materials, plus a selection of commercial campaigns were utilized to prompt discussion within the groups. The discussion allowed the exploration of girls' and young women's motivators (enabling and reinforcing factors) for personal health behaviours, attitudes and responses to health promotion materials, and the longer-term impacts of health promotion campaigns. A self-administered questionnaire was distributed at the commencement of each focus group, which provided additional information and was later triangulated with the qualitative data.Limitations due to the cross-sectional nature and sampling process of the study mean the results cannot be generalized beyond the study population. However the findings demonstrated that young women are motivated by a complex set of factors. The most common factors influencing the study groups were body image, self-esteem, media and role models.In addition young women of all age groups had a high awareness of the available messages in the areas studied. All groups discussed the increasing volume of health information available that is targeted at women. Participants noted much of the information originated from commercial sources. This in addition to public health initiatives resulted in increased 'health noise' to which they 'switched off'.Furthermore the YW&HP study revealed the importance of written media for women. The young women in this study appreciated the need for mass media advertising, however, preferred to have take-home advice to process at their own time. Discussion of how women process information revealed these young women to be a critical and analytical audience that are often skeptical of health information. Prior to making a decision, therefore, most of the women underwent a process of internal and external validation which included cross referencing information with peers, friends, family and health professionals to establish its accuracy, credibility and validity. Hence the findings of this study would support the need for further exploration of media such as women's magazines to promote health to young women which may in turn prompt discussion with peers and therefore expedite the validation process.Due to study limitations, results from this formative research need to be interpreted with caution. The results, however, would indicate the area of health promotion and how it communicates health information to young women would benefit from further investigation. The findings suggest many types of media currently being used to communicate health information to young women were useful and appropriate, specifically the use of social marketing media, which, was seen as a worthwhile and necessary strategy for this target group. Methods routinely used by commercial companies were also viewed as effective especially the use of women's magazines. As part of a comprehensive health promotion approach, this is a strategy, which may be an equally useful vehicle for public health messages.In conclusion, discussion with participants revealed a number of negative and positive unintended consequences. This would, therefore, support the need for further research in this area. Furthermore, the research has highlighted the importance of a comprehensive approach to the delivery of health information to young women. Best practice suggests this approach should adhere to ethical communication principles, which would enhance the intended outcomes of the communications whilst also assisting to maximize positive unintended consequences and minimize negative unintended consequences.